Contribution of muscle stiffness of the triceps surae to passive ankle joint stiffness in young and older adults - Hirata, Kosuke; Akagi, Ryota (Frontiers in Physiology, 2022)
This study aimed to investigate whether triceps surae muscle stiffness is associated with passive ankle joint stiffness in 40 young (21–24 years) and older (62–83 years) males. Using ultrasound shear wave elastography, the shear modulus of each muscle of the triceps surae (the medial [MG], lateral gastrocnemius [LG], and soleus [Sol]) was assessed as muscle stiffness at the ankle neutral position (NP) and 15-degree dorsiflexed position (DF15) with the knee fully extended. Passive ankle joint stiffness at NP and DF15 was calculated as the gradient of the angle-torque relationship at each joint angle during passive ankle dorsiflexion at 1 degree∙s-1 controlled by an isokinetic dynamometer. Passive ankle joint stiffness was normalized by the body mass. There was no correlation between the absolute ankle joint stiffness and muscle shear modulus of triceps surae in the young and older groups at NP (r ≤ 0.349, P ≥ 0.138). Significant positive correlations between absolute ankle joint stiffness and muscle shear modulus at DF15 were observed for MG and Sol in the young group (r ≥ 0.451, P ≤ 0.044) but not in the older group. The normalized ankle joint stiffness at NP was significantly positively correlated with the LG shear modulus in young participants and with the MG and LG shear modulus in older participants (r ≥ 0.466 and P ≤ 0.039). There were significant positive correlations between the normalized ankle joint stiffness and the muscle shear modulus of the triceps surae at DF15 in young and older participants (r ≥ 0.464 and P ≤ 0.040), except for the MG shear modulus in older participants (r = 0.419 and P = 0.066). These results suggest that the material properties of the entire triceps surae, even Sol, which is the most compliant muscle among the triceps surae, affect passive ankle joint stiffness, especially when the triceps surae is lengthened and body size is considered.